A Low Free T3 to Free T4 Ratio Is Associated with Sarcopenia in Euthyroid Patients with Type 2 Diabetes Mellitus. (17th August 2022) - Wang, Kewei; Zhang, Di; Cao, Guanglei; Wang, Chuan; Wang, Lingshu; Zhao, Ruxing; He, Qin; Hou, Xinguo; Gong, Lei; Chen, Li
Abstract : Background. This research evaluated the link between normal thyroid hormone levels and sarcopenia in patients with type 2 diabetes mellitus (T2DM). Methods. This cross-sectional study enrolled 312 euthyroid patients with T2DM from Qilu Hospital of the Shandong University, China. Body composition, grip strength, and physical performance were assessed as per the 2019 consensus guidelines of the Asian Working Group for Sarcopenia. Binary logistic regression was used to examine the correlation between thyroid hormone levels and sarcopenia and its components. Results. The prevalence of sarcopenia was 26.9%. Following adjustments for potential confounders, a high-normal serum free triiodothyronine (FT3) level (odds ratio OR = 0.522, 95% confidence interval (CI): 0.304–0.895, P = 0.018 ), a low-normal serum free thyroxine (FT4) level (OR = 1.126, 95% CI: 1.009–1.258, P = 0.034 ), and a heightened FT3/FT4 ratio (OR = 0.923, 95% CI: 0.879–0.969, P = 0.001 ) were linked to a low prevalence of sarcopenia. Considering the components of sarcopenia, FT3 concentration was positively associated with muscle strength (OR = 0.525, 95% CI: 0.305–0.902, P = 0.020 ) and physical performance (OR = 0.443, 95% CI: 0.259–0.758, P = 0.003 ), while FT4 concentration was negatively linked to muscle mass (OR = 1.114, 95% CI: 1.009–1.232, P = 0.036 ). The FT3/FT4 ratio was positively linked to muscle mass (OR = 0.943, 95% CI: 0.905–0.981, P = 0.006 ), muscle strength (OR = 0.945, 95% CI: 0.901–0.992, P = 0.021 ), and physical performance (OR = 0.934, 95% CI: 0.894–0.975, P = 0.002 ). Nevertheless, thyroid-stimulating hormone concentration was not associated with sarcopenia. Conclusion. A high FT3/FT4 ratio was significantly linked to a lowered risk of sarcopenia in euthyroid patients with T2DM.